The Economic Transition of Romania from a Behavioural Economics Perspective - Paula-Elena Diacon (CES Working Papers, 2012)
The aim of this article is to briefly analyze the economic transition of Romania from a behavioural economics perspective. Despite the adverse effects experienced in the past regime, the paper finds out that the suitable macroeconomic policies implemented had fundamental effects, generating economic welfare and higher standards of living, life satisfaction, and happiness / subjective well-being.
Keywords: D03; O11; P20; 330; behavioural economics; economic transition; macroeconomic policies Romania